PENCEGAHAN TERJADINYA GANGGUAN MENTAL SERIUS PADA MASA PANDEMI COVID-19 MELALUI PENINGKATAN KEMAMPUAN SELF HELP PADA REMAJA - Ika Yuniar Cahyanti; Tri Kurniati Ambarini; Dhian Kusumastuti; Anang Arief Abdillah; Theodore Baswara (Universitas Mataram, 2022)
The COVID-19 pandemic has had an impact on various aspects of human life, including mental health issues. Teenagers are a group that also feels the impact of the COVID-19 pandemic. Some of the problems faced by teenagers during the pandemic include changes in the learning environment that trigger a sense of laziness to fail in learning, addiction to online games, to problems in social interaction. The characteristics of adolescents who tend to be closed make the problems faced by adolescents are often unknown to teachers and parents. Therefore, this study aims to equip adolescents with knowledge about self-help abilities to prevent mental disorders in adolescents. Aspects of knowledge provided in this activity is knowledge about learning styles, assertiveness, and self-management. The activity was carried out for the students of MAN 2 Pontianak with the webinar method and discussion via WhatsApp group. There are a total of 15 pre-test and post-test data processed in this activity. The results show that there are differences in the average scores on all the variables measured in this activity, namely knowledge of learning styles, knowledge of assertiveness, knowledge of self-management, level of assertiveness and level of self-management. The analysis of the paired sample t-test difference test showed that the p value < 0.05 which indicated that there was a significant difference between learning style knowledge and self-management skill level between the pre-test and post-test sessions. In addition, the p value > 0.05 which indicates that there is no significant difference between assertiveness knowledge, assertiveness level and knowledge of self-management before and after intervention activities are given.